Development Finance and Aid in the Philippines: Policy, Institutional Arrangements and Flows - Gilberto M. Llanto; Adoracion M. Navarro; Ma. Kristina P. Ortiz (Philippine Institute for Development Studies (PIDS), 2015)
The Philippines' recent economic performance has been remarkable amid the lingering slowdown in the global economy and the devastation brought about by recent natural disasters. The economy grew by 7.2 percent in 2013, substantially higher than its 6.8 percent growth in 2012. With GDP growth averaging at 5.9 percent in the last three years, the Philippines is one of the better performers among the developing economies. However, the economy faces problems of high poverty incidence and income inequality. The main challenge is how to sustain rapid and inclusive growth.It is important for the government's inclusive growth strategy and development agenda to be supported by responsive development finance. This Development Finance and Aid Assessment prepared for the National Economic and Development Authority (NEDA) takes stock of current development finance in the Philippines. It provides a comprehensive survey of development finance and aid scenario in the Philippines in the next 5 to 10 years. It offers policy recommendations and proposals for enhancements on development financing in the country.
Keywords: 330; remittances; tax effort; Philippines; official development assistance (ODA); public-private partnership (PPP); inclusive growth; development finance; inclusive finance